Some theoretical issues regarding the ability of students to make career choices - Jovaiša, L. (Psichologija, 1965)
These issues are covered in the CPSU Central Committee and the USSR Council of Ministers theses: school life and the strengthening of communication, how schools must acquaint students with different types of work in society, as well as help them figure out their own inclinations and consciously choose a profession.These issues are linked to many pedagogical and psychological problems, such as what the psychological peculiarities of the choice of profession are, the pedagogical grounds for preparation of professional organization, the concept of vocational orientation, etc. Some of these problems have been successfully solved by Soviet educators and psychologists. Much work has been done investigating professional interests (K. Ariskina, M. Bieliajevas, L. Blagonadežina, V. Bobrova, M. Chomutova, A. Esaulovas, A. Ivaščenka, S. Kregždė, N. Levitovas, B. Stonys, L. Ziubinas, etc.), and some pedagogical and psychological orientation issues are being addressed (J. Averičevas, M. Vinogradova, A. Volkovskis, V. Čebyševa, A. Izmailovas, A. Šestelis, etc.). However, there is work that specially deals with the theoretical problems of vocational orientation. Therefore, the article intends to answer some theoretical questions regarding the principle and organization of the system of vocational orientation at an eight-year school.The article examines school-vocational orientation as a pedagogical activity that brings a learner to professional work, introduces a variety of professions, and teaches them to redirect their inclinations and strength, which allows students to consciously choose a profession that suits them and benefits society. The vocational orientation was carried out two different ways eight-year school, i.e., vocational guidance and career counseling.A profession is understood as a social activity, based on calling, carried out according to specialty and designed for the entire nation for the creation of material and spiritual goods.A calling should be considered as a strong affinity to certain spheres of work, a sense that the chosen profession is suitable and has a meaning in life. A calling is encouraged. A specialty is a skilled knowledge, abilities, and skills system related to a particular field of work.The last part of the article examines the psychological aspects of conscious choice of profession: the nature and importance of constant professional interests, inclination, and professional suitability. Professional suitability is physical, mental, and moral power to effectively develop the chosen vocation in useful work for the high quality benefit of society.The theoretical problem solving in this article is based on a dialectic materialistic social cultural development and the concept of human personality, Soviet and with foreign literature, but also some of our own research.
Keywords: vocational orientation; profession; professional interests; calling